Rebutting the suggestion that Anthony Giddens’s Structuration Theory offers a useful framework for sociological nursing research: a critique based upon Margaret Archer’s Realist Social Theory - Lipscomb, Martin (Nursing philosophy, 2006)
A recent paper in this journal by Hardcastle et al. in 2005 argued that Anthony Giddens’s Structuration Theory (ST) might usefully inform sociological nursing research. In response, a critique of ST based upon the Realist Social Theory of Margaret Archer is presented. Archer maintains that ST is fatally flawed and, in consequence, it has little to offer nursing research. Following an analysis of the concepts epiphenomenalism and elisionism, it is suggested that emergentist Realist Social Theory captures or describes a more coherent explanatory vision of social reality than other perspectives and nurse researchers are advised to consider its potential.